Knowledge of CPR and first aid for children among pedagogy students. - Daryna Sholokhova; Monika Michalak; Arkadiusz Wejnarski (Critical Care Innovations, 2023)
INTRODUCTION: At home, the parents take care of the child's safety, but when the child is in school or kindergarten, it is the educator that takes care of the child. The awareness of dangers the child is exposed to at every moment of his or her activity during the day obliges educators to have up-to-date knowledge of first aid. The marked differences in anatomy, physiology and mechanisms of life-threatening conditions make the principles of first aid differ from those of an adult. First aid courses organised for both educators and pedagogy students should focus on highlighting these differences and learning how to deal with individuals of all ages. The aim of the study is to assess the level of knowledge and practical skills among pedagogy students and to identify aspects requiring adjustments to the curriculum of future teachers. MATERIALS AND METHODS: The study was conducted in 2022 at the Institute of Pedagogy at the University of Siedlce, Poland. Sixty-three pedagogy students participated in it. For the purpose of the study, a survey questionnaire covering the principles of first aid for children and a practical task evaluation sheet were created. Practical skills were assessed using the Resusci Junior QCPR simulator and a 0-15 point rating scale. RESULTS: The study included as many as 63 students of early childhood and pre-school pedagogy. The mean score achieved on the theory test was M=11.49 out of a possible 14 points (SD±1.24). The highest number of correct answers were given by students for the following questions: actions performed when assessing the child's breathing (n=63; 100%) and placing the child in the safe position (n=61; 96.8%). In contrast, the fewest correct answers were related to the rate of chest compressions (n=27; 42.9%). In the practical task, as many as 15 child CPR activities were considered. The average points scored by students on the practical task was M=6.73 out of a possible 15 points (SD±2.73). The average quality of compressions performed was M=28.59% (SD±30.41), breaths M=17.7% (SD±17.70) and chest compression depth was M=20.29% (SD±27.98). CONCLUSIONS: The level of theoretical knowledge and practical skills of pedagogy students is clearly insufficient to provide effective first aid to children. Significant differences were observed among students taking first aid classes onsite versus remotely. Having theoretical knowledge does not translate into practical skills. It seems that it is necessary to modify the curriculum for training future educators in first aid for children.